An illustrated brief history of western philosophy 20th anniversary edition - Kenny, Anthony 1931- (Hoboken, NJ Wiley Blackwell, 2019)
Newly revised and expanded for a special 20th anniversary publication, the latest edition of An Illustrated Brief History of Western Philosophy contains all of Kenny's original writings on the history of Western philosophy from ancient to modern, along with new writings on the philosophy of the mid-20th century, covering important contributions from continental philosophers and philosophers of the post-Wittgenstein anglophone traditions including the work of many women who have too often been neglected by the historical record. - from bookjacket.
An Illustrated Brief History of Western Philosophy: 20th Anniversary Edition; Contents; Preface; List of Illustrations; Acknowledgements; Introduction; I: Philosophy In Its Infancy; The Milesians; Xenophanes; Heraclitus; The School of Parmenides; Empedocles; The Atomists; II: The Athens Of Socrates; The Athenian Empire; Anaxagoras; The Sophists; Socrates; The Euthyphro; The Crito; The Phaedo; III: The Philosophy Of Plato; Life and Works; The Theory of Ideas; Plato's Republic; The Theaetetus and the Sophist; IV: The System of Aristotle; Plato's Pupil, Alexander's Teacher; The Foundation of LogicThe Theory of Drama; Moral Philosophy: Virtue and Happiness; Moral Philosophy: Wisdom and Understanding; Politics; Science and Explanation; Words and Things; Motion and Change; Soul, Sense, and Intellect; Metaphysics; V: Greek Philosophy After Aristotle; The Hellenistic Era; Epicureanism; Stoicism; Scepticism; Rome and its Empire; Jesus of Nazareth; Christianity and Gnosticism; Neo-Platonism; VI: Early Christian Philosophy; Arianism and Orthodoxy; The Theology of Incarnation; The Life of Augustine; The City of God and the Mystery of Grace; Boethius and Philoponus; VII: Early Medieval PhilosophyJohn the Scot; Alkindi and Avicenna; The Feudal System; Saint Anselm; Abelard and He?loi?se; Abelard's Logic; Abelard's Ethics; Averroes; Maimonides; VIII: Philosophy in the Thirteenth Century; An Age of Innovation; Saint Bonaventure; Thirteenth-Century Logic; Aquinas' Life and Works; Aquinas' Natural Theology; Matter, Form, Substance, and Accident; Aquinas on Essence and Existence; Aquinas' Philosophy of Mind; Aquinas' Moral Philosophy; IX: Oxford Philosophers; The Fourteenth-Century University; Duns Scotus; Ockham's Logic of Language; Ockham's Political Theory; The Oxford Calculators John Wyclif; X: Renaissance Philosophy; The Renaissance; Free-will: Rome vs. Louvain; Renaissance Platonism; Machiavelli; More's Utopia; The Reformation; Post-Reformation Philosophy; Bruno and Galileo; Francis Bacon; XI: The Age of Descartes; The Wars of Religion; The Life of Descartes; The Doubt and the Cogito; The Essence of Mind; God, Mind, and Body; The Material World; XII: English Philosophy in the Seventeenth Century; The Empiricism of Thomas Hobbes; Hobbes' Political Philosophy; The Political Theory of John Locke; Locke on Ideas and Qualities; Substances and PersonsXIII: Continental Philosophy in the Age Of Louis XIV; Blaise Pascal; Spinoza and Malebranche; Leibniz; XIV: British Philosophy in the Eighteenth Century; Berkeley; Hume's Philosophy of Mind; Hume on Causation; Reid and Common Sense; XV: The Enlightenment; The Philosophes; Rousseau; Revolution and Romanticism; XVI: The Critical Philosophy of Kant; Kant's Copernican Revolution; The Transcendental Aesthetic; The Transcendental Analytic: The Deduction of the Categories; The Transcendental Analytic: The System of Principles.
Mr. Noe Santillan (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Philosophy -- History